КРИТИКАЛЫҚ ПИКИРЛЕЎДИ РАЎАЖЛАНДЫРЫЎ ТЕХНОЛОГИЯСЫН ҚОЛЛАНЫЎ АРҚАЛЫ ЖАСЛАРДА КИТАП ОҚЫЎҒА БОЛҒАН ҚЫЗЫҒЫЎШЫЛЫҚТЫ ҚӘЛИПЛЕСТИРИЎ - Ешниязова, Э.Н. (FAN va JAMIYAT, 2024)
This article analyzes the features of the thinking of modern youth, characterizes the specifics of clip thinking, and also discusses the issues of developing interest in reading fiction among young people through the use of technology for the development of critical thinking.